Territorial Cohesion - Scholich, Dietmar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The various regions within the EU are marked by a high degree of disparity with regard to their economic performance and productivity, and as regards their labour markets. Facing these regional differences, the task of regional and spatial sciences is to develop concepts and strategies to reduce and prevent territorial imbalances. Thus "territorial cohesion" stands for a more balanced spatial development, and aims to improve integration throughout the EU. Although the term is used in many EU documents and strategies, its meaning remains vague and unclear. The scientific articles in this annual deal with the interpretations of this term, the challenges of European spatial development policy, and the problems and concepts involved in achieving territorial cohesion. Furthermore two short reports illustrate the implementation of territorial cohesion on the basis of two research projects.
Preface $1 (BIntroduction -- Preface $1 (BIntroduction -- Refereed Section -- Status and Perspectives of Territorial Cohesion with Respect to European Spatial Development Policy (ESDP) $1 (BNormative and Governance Aspects -- Territorial Cohesion $1 (BBetween Expectations, Disparities and Contradictions -- Regional Disparities $1 (BReasons Enough to Run a Cohesion-Oriented Spatial Policy? -- Territorial Cohesion, Brain Drain and Digital Divide -- Environmental Protection needs good Administration: Ecological Applications of the New Legal Instrument (3z(BEuropean Groupings of Territorial Co-operation (EGTC)(3y (B-- Suburbanisation, Suburbia and (3z(BZwischenstadt(3y(B: Perspectives of Research and Policy -- Varying Costs of Living as Compensation for Regional Disparities in Germany -- Territorial Cohesion and Transboundary Governance: Insights from the Polish-German and the Czech-German Borders -- Short Reports -- Spatial Development Strategies in the Enlarged EU: ESPON Project 1.2.3 on Spatially Relevant Aspects of the Information Society -- IRS Participates in EU-funded Research Project (3z(BGovernance for Sustainability(3y(B.s
Keywords: Geography; Regional planning; Urban planning; Civil engineering; Environmental law; Environmental policy; Regional economics; Spatial economics; Human geography; Geography; Landscape/Regional and Urban Planning; Geography, general; Civil Engineering; Regional/Spatial Science; Human Geography; Environmental Law/Policy/Ecojustice.; Electronic books